The relationship between running speed and measures of veritcal jump in professional basketball players - Shalfawi, S.; Enoksen, E.; Tonnesen, E. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
To examine the relationship between leg-power, jumping height, and reactive strength as measures of jumping performance with sprint speed over 10-m, 20-m, and 40-m. These distances are considered to be indicative of starting speed, initial acceleration, and maximum sprinting speed capabilities, respectively, of the athlete.[1,2] Participants: Thirty three male professional basketball players who have been professionals for at least two years. Design: The subjects were tested on 10-m, 20-m, and 40-m sprint, counter-movement jump (CMJ), and static vertical jump (SJ). Jumping height, peak power, and reactive strength were obtained from the measurements of CMJ and SJ. All participants have been involved in intensive resistance and sprint training three times a week, and were considered to be in peak condition at the time of testing. Tests were carried out in an inside court, which was 70-m in length and 40-m in width. Results: The results indicate that there was a marked relationship between sprinting speed and measures of peak power relative to body mass (P<0.05), but no marked relationship with peak power in absolute terms. Measures of jumping height had a marked relationship with sprinting speed in both absolute terms and relative to body mass. None of the reactive strength measures had a notable relationship with sprinting performance. Furthermore, the results showed that concentric contraction is of greater importance for starting and acceleration speed from zero to 10-m than for acceleration and top speed through 20-m to 40-m. And the eccentric followed by concentric contraction was of greater importance for the top running speed from 20-m to 40-m than for start and acceleration speed. However, the results indicate that the more the athlete increases in acceleration speed, the more important relative power becomes to performance during acceleration. Conclusions: The results of this study indicate that while there is a strong and marked relationship between 10-m, 20-m and 40-m sprint, there is also a considerable variation within the factors that contribute to performance over these distances. This may indicate that, separate training strategies could be implemented to improve running speed over these distances. Furthermore, it is recommended that when attempting to increase running speed, special attention should be paid to power per kilogram of body mass of the athlete. However, strength and conditioning coaches may need to implement a concentric only and stretch shortening cycle jump squat testing battery to better analyze and plan the sprint and resistance training.